ANALYSIS OF THE EFFECT OF SERVICE QUALITY AND PRICE ON LOYALTY THROUGH CUSTOMER SATISFACTION IN PADANG RESTAURANT IN MAKASSAR - Nurul Lathifah; Sumardi Lasise; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to analyze the effect of service quality and price on customer loyalty through customer satisfaction with Padang restaurants in the city of Makassar. This study takes data directly from the number of customers who eat at several Padang restaurants, especially in the city of Makassar by taking 100 customers from 3 different restaurants as samples in this study. To implement the objectives of this study used analysis techniques using path analysis. The results of the analysis prove that service quality (X1) on customer loyalty (Z) through customer loyalty (Y) has a positive and significant effect. The effect of price (X2) on customer loyalty (Z) through customer loyalty (Y) has a positive and significant effect, but the effect of service quality (X1) on customer satisfaction (Z) has a negative and insignificant effect.